Clinical utility of tadalafil in the treatment of pulmonary arterial hypertension: an evidence-based review - Henrie, Adam M (Core Evid, 2015)
Pulmonary arterial hypertension (PAH) is a chronic and disabling condition characterized by an elevated pulmonary vascular resistance and an elevated mean pulmonary arterial pressure. Despite recent improvements in treatment availability, PAH remains challenging to treat, burdensome for patients, and ultimately incurable. Tadalafil is a phos-phodiesterase-5 inhibitor that is administered once daily by mouth for the treatment of PAH. Current treatment guidelines recommend tadalafil as an option for patients with World Health Organization functional class II or III PAH. In a placebo-controlled clinical trial, patients taking tadalafil demonstrated significantly improved exercise capacity as measured by the 6-minute walk distance. Patients also experienced decreased incidence of clinical worsening, increased quality of life, and improved cardiopulmonary hemodynamics. Uncontrolled studies and smaller trials have indicated a possible role for tadalafil as a suitable alternative to sildenafil and as a beneficial add-on option when used in combination with other treatments for PAH. Tadalafil is generally safe and well tolerated. Adverse events are typically mild-to-moderate in intensity, and discontinuation rates are usually low. The purpose of this review is to provide an evidence-based evaluation of the clinical utility of tadalafil in the treatment of PAH.